1999
DOI: 10.1034/j.1399-3070.1999.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophic activities in tropical landfill cover soils: effects of temperature, moisture content and methane concentration

Abstract: The methane oxidizing capacity of landfill cover soils was investigated through column and batch experiments by simulating conditions that are usually encountered in tropical climates. The rate of oxidation was monitored at different temperatures and moisture contents. It was observed that a low moisture content of 6% produced negligible oxidation, whereas oxidation rates were at a maximum at moisture contents between 15 and 20%. Temperature was found to be a dominant parameter which controlled the oxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 16 publications
(32 reference statements)
5
58
0
1
Order By: Relevance
“…Both low and high soil moisture levels can negatively impact soil uptake of atmospheric CH 4 (Schnell and King, 1996;von Fischer et al, 2009). Scarcity of soil water generally inhibits soil microbial activity while excessive moisture attenuates gas diffusion, limiting entry of atmospheric CH 4 and O 2 into soil (Burke et al, 1999;McLain et al, 2002;McLain and Ahmann, 2007;West et al, 1999).…”
Section: Soil Moisture Factor R Smmentioning
confidence: 99%
See 2 more Smart Citations
“…Both low and high soil moisture levels can negatively impact soil uptake of atmospheric CH 4 (Schnell and King, 1996;von Fischer et al, 2009). Scarcity of soil water generally inhibits soil microbial activity while excessive moisture attenuates gas diffusion, limiting entry of atmospheric CH 4 and O 2 into soil (Burke et al, 1999;McLain et al, 2002;McLain and Ahmann, 2007;West et al, 1999).…”
Section: Soil Moisture Factor R Smmentioning
confidence: 99%
“…16) to account for decreased gas diffusion and limitation of k d at high soil moisture content. However, attenuation of gas diffusion is only one impact of high soil water content and it is necessary also to account for the inhibitory effects of excessive moisture on k d (Boeckx and Van Cleemput, 1996;van den Pol-van Dasselaar et al, 1998; Visvanathan et al, 1999). Soil moisture content > 20 % reduces CH 4 uptake due to a restricted diffusion of CH 4 and supply of O 2 .…”
Section: Soil Moisture Factor R Smmentioning
confidence: 99%
See 1 more Smart Citation
“…The CH 4 oxidation capacity of landfill cover soils varies within and among landfills due to many factors that affect the oxidation process, such as seasonal variations (Abushammala et al, 2013b;Einola et al, 2007;Maurice and Lagerkvist, 2003;Börjesson et al, 2001), physical and chemical heterogeneities of landfill cover soils (Tecle et al, 2008;Albanna et al, 2007;Visvanathan et al, 1999), and the CH 4 concentrations in landfills (Boeckx et al, 1996). According to Mosier et al (2004), the major factors controlling CH 4 oxidation are potential biological demand and diffusion.…”
Section: Factors Affecting Methane Oxidationmentioning
confidence: 99%
“…The CH 4 oxidation rate increases with increasing soil organic content (Humer and Lechner, 2001;Christophersen et al, 2000;Visvanathan et al, 1999 soil incubation tests, Christophersen et al (2000) found that soils containing more organic matter more effectively mitigate CH 4 emissions through oxidation. They also found a relationship between the optimal soil moisture content and the organic matter content.…”
Section: Soil Organic Contentmentioning
confidence: 99%